Optimal simple objectives for monetary policy when banks matter - Laureys, Lien,Meeks, Roland,Wanengkirtyo, Boromeus (International Monetary Fund, 2020)
We reconsider the design of welfare-optimal monetary policy when financing frictions impair the supply of bank credit, and when the objectives set for monetary policy must be simple enough to be implementable and allow for effective accountability. We show that a flexible inflation targeting approach that places weight on stabilizing inflation, a measure of resource utilization, and a financial variable produces welfare benefits that are almost indistinguishable from fully-optimal Ramsey policy. The macro-financial trade-off in our estimated model of the euro area turns out to be modest, implying that the effects of financial frictions can be ameliorated at little cost in terms of inflation. A range of different financial objectives and policy preferences lead to similar conclusions
10.5089/9781513561172.001
Keywords: Graue Literatur; Business and Economics; Money and Monetary Policy; Economic Theory; Production and Operations Management; General Aggregative Models: Forecasting and Simulation; Monetary Policy; Central Banks and Their Policies; Banks; Depository Institutions; Micro Finance Institutions; Mortgages; Macroeconomics: Production; Price Level; Deflation; Financial Economics; Macroeconomics; Economic theory & philosophy; Monetary economics; Output gap; Inflation; Financial frictions; Inflation targeting; Production growth; Production; Economic theory; Production; Economic theory; Prices; Economic forecasting; Monetary policy; Simple loss function; Medium-scale DSGE models; Euro area economy